Environmental Health in Emergencies and Disasters. - Organization, World Health (World Health Organization, 2003)
This volume distills what is known about environmental health during an emergency or disaster. It draws on results from the International Decade for Natural Disaster Reduction, and on experience with sustainable development between the two Earth Summits, in Rio de Janeiro and Johannesburg. It is intended for practitioners, as well as for policy-makers and researchers, and thus covers both general and technical aspects of environmental health. In Part I of this volume, a conceptual framework is presented for understanding environmental health issues in the context of disaster management. The fr.